On the crustal structure of the eastern Himalayas adjoining Tibetan Plateau and Chinese mountain (MAUSAM, 1976)
The crustal structure of the eastern Himalayas, adjoining Tibetan Plateau and Chinese mountains has been investigated from body wave data of near earthquakes. A three  layered crustal model consisting of two granitic layers (granite I and II) and one basaltic layer has been interpreted. Wave velocities for Pg1, Pg2, P and Pn phases have been observed to be as 5.65, 6.03, 6.49 and 7.97 km/sec and for Sgl', Sg2' S, tunnel to than Sn phases to be as 3.42, 3.60,3.90 and 4.53 km/sec respectively. It has also been observed that the wave velocity increases with depth in the granite I layer. The average thickness of the crustal layers for granite I are found to be as 22.0 km, for granite II as 12.3 km and for basaltic layer as 16.1 km. The average depth of the, M-discontinuity in the region has been interpreted as 504 km. It has also been observed that the crust-mantle boundary dips at an angle of about 30' from south to north along Long. 103°E. A general thickening of the crust has also been observed in the eastern Himalayas from Kunming towards Lhasa.